Representation Analysis of “Great Expectation” Novel by Charles Dickens - Luthfiansyah Luthfiansyah; Mildan Arsdan Fidinillah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
This research examines the novel ‘The Great Expectation’. Researchers are interested in analyzing this novel because it is a picture of real life, especially life in the United Kingdom in the days of Queen Victoria. As a realistic writer, Charles Dickens is through people’s descriptions reflect reality in his life time. This research uses the theory of semiotics which is collaborated with Karl Marx’s theory which reveals class strata. In the science of semiotics, everything, even humans can be made a sign, which can be developed into a myth of life. Seeing from the main actor’s novel, Pip, Everyone still has a lot to learn, such as his kindness, strength, and optimism. Individual growth is the process of growing into a perfect self. Although Pip’s great hopes are disappointing, he finally returns to good moral character, and starts a new life. In addition, this study analyzes the style of the main character Pip which has its own points in interpreting the style of dress. In this novel, researchers want to prove that the style of dress can be a tool to prove the formation of a person’s identity or the identity of a particular group that uses it.